Lixisenatide resensitizes the insulin‐secretory response to intravenous glucose challenge in people with type 2 diabetes – a study in both people with type 2 diabetes and healthy subjects1. Issue 9 (25th March 2014) - Becker, R. H. A.; Stechl, J.; Msihid, J.; Kapitza, C.
<x xml:space="preserve">Abstract</x> Aims Glucagon‐like peptide‐1 (GLP‐1) receptor agonists improve blood glucose control by enhancing glucose‐sensitive insulin release, delaying gastric emptying and reducing postprandial glucagon secretion. The studies reported here investigated the insulin response to an intravenous (iv) glucose challenge after injection of lixisenatide (LIXI) 20 µg or placebo. Methods Two single‐centre, double‐blind, randomized, placebo‐controlled, single‐dose, crossover studies were performed in healthy subjects (HS) and people with type 2 diabetes mellitus (T2DM). Participants received subcutaneous LIXI or placebo 2 h before an iv glucose challenge. Study endpoints included first‐ and second‐phase insulin response, insulin concentration (INS), glucagon response and glucose disposal rate (Kglucose). LIXI exposure was measured over 12 h. Results LIXI 20 µg reached maximum concentration after 2 h and resensitized first‐phase insulin secretion by 2.8‐fold in T2DM to rates comparable with those in HS on placebo, and raised second‐phase insulin secretion by 1.6‐fold in T2DM. INS rose correspondingly and glucose disposal was accelerated by 1.8‐fold in T2DM. First‐phase insulin secretion and glucose disposal were also augmented by LIXI in HS, whereas second‐phase insulin secretion reduced blood glucose concentrations to below fasting levels and then ceased, accompanied by a rapid, short‐lasting rise in glucagon. Otherwise, suppression of glucagon release subsequent to augmentation of insulin release was unaffected in T2DM and in HS. Conclusions LIXI resensitized the insulin response to an iv glucose challenge in people with T2DM, thereby accelerating glucose disposal to nearly physiological intensity, and did not impair counter‐regulation to low glucose levels by glucagon.